Jawabanmu

2014-05-17T12:17:33+07:00
PH = 10
pOH = 14-pH= 4
[OH⁻] = 10⁻⁴
Mg(OH)₂ ---------] Mg²⁺ + 2OH⁻
[Mg²⁺] = 1/2 [OH⁻] = 1/2 x 10⁻⁴
Ksp = [Mg²⁺][OH⁻]²
       = 5 x 10⁻¹³ (E)
2 3 2
Jawaban paling cerdas!
2014-05-17T12:38:23+07:00
pH Mg(OH)2 = 10 --> pOH = 4
maka [OH^-] = 1 x 10^-4 M

Mg(OH)2 (s) --> Mg^2+ (aq)      +      2OH^- (aq)
1/2 x 10^-4 M    1/2 x 10^-4 M           1 x 10^-4 M

Ksp = [Mg^2+][OH^-]^2
       = (1/2 x 10^-4)(1 x 10^-4)^2
       = 1/2 x 10^-4 x 1 x 10^-8
       = 0,5 x 10^-12
       = 5 x 10^-13  (E)